Genome-wide analysis of transmembrane 9 superfamily genes in wheat (Triticum aestivum) and their expression in the roots under nitrogen limitation and Bacillus amyloliquefaciens PDR1 treatment conditions - Li, Fei; Xi, Kuanling; Li, Yuke; Ming, Tang; Huang, Yufeng; Zhang, Lijun (Frontiers in Plant Science, 2024)
Introduction Transmembrane 9 superfamily (TM9SF) proteins play significant roles in plant physiology. However, these proteins are poorly characterized in wheat (Triticum aestivum). The present study aimed at the genome-wide analysis of putative wheat TM9SF (TraesTM9SF) proteins and their potential involvement in response to nitrogen limitation and Bacillus amyloliquefaciens PDR1 treatments. Methods TraesTM9SF genes were retrieved from the wheat genome, and their physiochemical properties, alignment, phylogenetic, motif structure, cis-regulatory element, synteny, protein-protein interaction (PPI), and transcription factor (TF) prediction analyses were performed. Transcriptome sequencing and quantitative real-time polymerase reaction (qRT-PCR) were performed to detect gene expression in roots under single or combined treatments with nitrogen limitation and B. amyloliquefaciens PDR1. Results and discussion Forty-seven TraesTM9SF genes were identified in the wheat genome, highlighting the significance of these genes in wheat. TraesTM9SF genes were absent on some wheat chromosomes and were unevenly distributed on the other chromosomes, indicating that potential regulatory functions and evolutionary events may have shaped the TraesTM9SF gene family. Fifty-four cis-regulatory elements, including light-response, hormone response, biotic/abiotic stress, and development cis-regulatory elements, were present in the TraesTM9SF promoter regions. No duplication of TraesTM9SF genes in the wheat genome was recorded, and 177 TFs were predicted to target the 47 TraesTM9SF genes in a complex regulatory network. These findings offer valued data for predicting the putative functions of uncharacterized TM9SF genes. Moreover, transcriptome analysis and validation by qRT-PCR indicated that the TraesTM9SF genes are expressed in the root system of wheat and are potentially involved in the response of this plant to single or combined treatments with nitrogen limitation and B. amyloliquefaciens PDR1, suggesting their functional roles in plant growth, development, and stress responses. Conclusion These findings may be vital in further investigation of the function and biological applications of TM9SF genes in wheat.